A Data Security System in The Domain of Online Data Storage (International Journal of Food and Nutritional Sciences, 2022)
Data security is a collection of protocols and tools that guard against the accidental or purposeful loss, alterations, or disclosure of data. Control activities, physical security, logical controls, organizational standards, and other protecting approaches that restrict access to unauthorized or malicious persons or processes are only a few of the methods and technologies that may be used to apply data security. In the context of big data, this article gives an overview of data security and data quality. By highlighting the potential conflicts that may arise during the installation of data security and data quality control systems, the author hopes to draw attention to them. Conflict of this nature increases complexity and demands unique, customized solutions. The future scope of this study Information and communications technology (ICT) has been used more often recently by state authorities as well as the corporate sector to access personal data. Data is a crucial component of freedom for both private and public goals.